Herding on fundamental information: A comparative study - Galariotis, Emilios C.; Rong, Wu; Spyrou, Spyros I. (Journal of Banking & Finance, 2015)
This paper tests for herding towards the market consensus for US and UK leading stocks, and to the best of our knowledge addresses a gap in the literature regarding the importance of major fundamental macroeconomic announcements. The results indicate that US investors tend to herd during days when important macro data are released, and that there have been herding spill-over effects from the US to the UK during earlier financial crises. Further results reveal more differences in herding behavior between the two markets: in the US we find that investors herd due to both fundamentals and non-fundamentals during different crises, when in the UK there is herding only due to fundamentals and only during the Dotcom bubble burst. These results suggest that the drivers of herding behavior are period and country specific.